Islamic Bank and Monetary Policy: The Case of Indonesia - Regi Muzio Ponziani; Tatik Mariyanti (Universitas Muhammadiyah Yogyakarta, 2020)
Islamic bank in Indonesia exists side by side with its conventional counterpart within dual banking system, while the central bank aims to achieve price stability in the economy using conventional and Islamic monetary instruments within dual monetary system. This posits a very unique environment for Islamic bank. This research aims to examine the role of Islamic bank in monetary policy transmission mechanism using Granger Causality and Autoregressive Distributed Lag (ARDL). The balance sheet components of deposit and financing were hypothesized to function in monetary transmission process within bank financing channel. Granger causality revealed that Islamic interbank overnight rate granger causes Islamic deposit and financing. Islamic deposit and financing granger cause industrial production index. Industrial production index granger cause inflation, Islamic deposit, and Islamic interbank overnight rate. Islamic deposit and inflation granger cause Islamic interbank overnight rate. The ARDL results showed that there were cointegrating relationships in the output and inflation model. Long-term convergence could be reached to correct deviations in output and inflation by way of Islamic banks’ deposit and financing. However, short-term influence is contributed only by Islamic banks’ deposit to output. Islamic banks’ deposit does not contribute in the short-run to inflation. Islamic banks’ financing does not have short-term relationship with output and inflation. Hence, there is a declining effectiveness of Islamic banks’ financing contribution to the economy.